Novel Metal Complexes Derived from Selenosemicarbazone Ligand; Synthesis, Spectral Investigation and Biological Activity - Talib H. Mawat (Journal of Global Pharma Technology, 2019)
The formation of a novel bidentate Schiff-base seleno-ligand (HL) and its metal complexes are reported. The title ligand (E)-2-((R)-2-((R)-(4-(dimethylamino)phenyl)((3-nitrophenyl)amino)- methyl)cyclohexylidene)hydrazine-1-carboselenoamide (HL) was prepared from the reaction of 2-((4-(dimethylamino) phenyl) ((3-nitrophenyl)amino) methyl) cyclohexan-1one with KSeCN and NH2NH2 in a 1:1:3 mole ratio using a mixture of CHCl3:EtOH (1:3) as a medium. The reaction of the ligand with Mn(II), Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) metal ions in a 2:1 (L:M) mole ratio resulted in the isolation of new selenosemicarbazone complexes of general formula K2[ML2Cl2] and [M`L2], (M= Mn(II), Co(II) and Ni(II); M`= Cu, Zn and Cd). A range of physico-chemical methods were used to predict the geometry of complexes. These analyses indicated the formation of octahedral, square planar and tetrahedral geometry about (Mn(II), Co(II) and Ni(II)), Cu(II) and (Zn(II), Cd(II)) ions, respectively. The thermal analysis of the ligand and some metal complexes were investigated to check the stability of tested compounds. Biological activity of the ligand (HL) and its metal complexes against Gram negative bacterial strains; E. coli, B. sabtuius and K. Pneumoniae and Gram positive species; St. aureus were studied. The compounds displayed various activity towards tested bacteria. Further, selenosemicarbazone compounds were examined against four fungus species (Candida albicans, Candida glabrata, Candida tropicalis and Candida parapsilsis). More, the tested compounds showed activity towards all four fungus species (except Co(II)-complex that showed no activity against Candida tropicalis).Keywords: Selenosemicarbazone ligand; Metal complexes; Structural study; Biological activity.